Home Is Where the School Is : The Logic of Homeschooling and the Emotional Labor of Mothering - Lois, Jennifer (Book collections on Project MUSE., 2013)
Mothers who homeschool their children constantly face judgmental questions about their choices, and yet the homeschooling movement continues to grow with an estimated 1.5 million American children now schooled at home. These children are largely taught by stay-at-home mothers who find that they must tightly manage their daily schedules to avoid burnout and maximize their relationships with their children, and that they must sustain a desire to sacrifice their independent selves for many years in order to savor the experience of motherhood. This book is a comprehensive look into the lives of homeschooling mothers.